Bronchoscopic guidance of endovascular stenting limits airway compression. Issue 5 (27th December 2014) - Ebrahim, Mohammad; Hagood, James; Moore, John; El‐Said, Howaida
Abstract : Objective: Bronchial compression as a result of pulmonary artery and aortic arch stenting may cause significant respiratory distress. We set out to limit airway narrowing by endovascular stenting, by using simultaneous flexible bronchoscopy and graduated balloon stent dilatation, or balloon angioplasty to determine maximum safe stent diameter. Methods: Between August 2010 and August 2013, patients with suspected airway compression by adjacent vascular structures, underwent CT or a 3D rotational angiogram to evaluate the relationship between the airway and the blood vessels. If these studies showed close proximity of the stenosed vessel and the airway, simultaneous bronchoscopy and graduated stent re‐dilation or graduated balloon angioplasty were performed. Results: Five simultaneous bronchoscopy and interventional catheterization procedures were performed in four patients. Median age/weight was 33 (range 9–49) months and14 (range 7.6–24) kg, respectively. Three had hypoplastic left heart syndrome, and one had coarctation of the aorta (CoA). All had confirmed or suspected left main stem bronchial compression. In three procedures, serial balloon dilatation of a previously placed stent in the CoA was performed and bronchoscopy was used to determine the safest largest diameter. In the other two procedures, balloon testing with simultaneous bronchoscopy was performed to determine the stent size that would limit compression of the adjacent airway. In all cases, simultaneous bronchoscopy allowed selection of an ideal caliber of the stent that optimized vessel diameter while minimizing compression of the adjacent airway. Conclusion: In cases at risk for airway compromise, flexible bronchoscopy is a useful tool to guide endovascular stenting. Maximum safe stent diameter can be determined without risking catastrophic airway compression. © 2014 Wiley Periodicals, Inc.